2021
DOI: 10.1038/s41467-020-20543-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcription shapes genome-wide histone acetylation patterns

Abstract: Histone acetylation is a ubiquitous hallmark of transcription, but whether the link between histone acetylation and transcription is causal or consequential has not been addressed. Using immunoblot and chromatin immunoprecipitation-sequencing in S. cerevisiae, here we show that the majority of histone acetylation is dependent on transcription. This dependency is partially explained by the requirement of RNA polymerase II (RNAPII) for the interaction of H4 histone acetyltransferases (HATs) with gene bodies. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 78 publications
10
98
4
Order By: Relevance
“…This is consistent with a previous study of a mixed population of saturated cultures where histone acetylation was found to occur later in exit [44]. Together, our results are in agreement with a recent study demonstrating that histone acetylation takes place mostly as a consequence of transcription [45].…”
Section: Chromatin Bears Hallmarks Of Repression During Early Quiescent Exit Time Pointssupporting
confidence: 94%
“…This is consistent with a previous study of a mixed population of saturated cultures where histone acetylation was found to occur later in exit [44]. Together, our results are in agreement with a recent study demonstrating that histone acetylation takes place mostly as a consequence of transcription [45].…”
Section: Chromatin Bears Hallmarks Of Repression During Early Quiescent Exit Time Pointssupporting
confidence: 94%
“…This is consistent with a previous study of a mixed population of saturated cultures where histone acetylation was found to occur later in exit[44]. Together, our results are in agreement with a recent study demonstrating that histone acetylation takes place mostly as a consequence of transcription [45].…”
Section: Resultssupporting
confidence: 94%
“…This suggests that, while there was a strong transcriptional response during refeeding, histone acetylation was delayed. This result is in agreement with a recent study demonstrating that histone acetylation takes place mostly as a consequence of transcription [44].…”
Section: Chromatin Bears Hallmarks Of Repression During Early Quiescent Exit Time Pointssupporting
confidence: 94%
See 2 more Smart Citations